Tekanan dalam Bahasa Tontemboan: Pendekatan Fonetik Eksperimental - Robot, Kevin Yeremia; Kalangi, Leika Maria Victoria; Imbang, Djeinnie (Kajian Linguistik, 2019)
Stress is one of suprasegmental feature in language and is included in the study of acoustic phonetics. Tontemboanese is a language spoken in several areas in Minahasa, and in this research, the word stress in Tontemboanese is done through the approach of experimental phonetics by employing the software Praat in data analysis. The data are collected through recording from interview, cut the recording into several one-word recordings, and then the data are analyzed with Praat to determine the pitch, duration, and intensity of each syllable. Through the data analysis, it is found that the Tontemboanese word stress is a fixed word stress, and the position of the stress is generally in the penultimate syllables. The result is still similar with the results by Schwarz (1908) and Tambuwun (1986) which states that the word stress in Tontemboanese is in the penultimate syllable. Keywords: Stress, Suprasegmentals, Tontemboan, Experimental Phonetics